Phenolics in Mediterranean and Middle East Important Fruits. (3rd May 2020) - Haddad, Moawiya A; El-Qudah, Jafar; Abu-Romman, Saeid; Obeidat, Maher; Iommi, Candela; Jaradat, Da'san M M
Abstract: Background: Phenolic compounds (polyphenols) are common plant secondary metabolites playing different roles in plants, and some of these vegetables and correlated fruits—figs, grapes, pomegranates, olives, date palms, etc.—contain remarkable and diversified amounts of these substances. In addition, polyphenols are reported to show positive effects for human health, because of their antioxidant behavior. Figs are an excellent source of polyphenols with highest concentrations of proanthocyanidins. Actually, figs contain higher amounts of polyphenols than red wine and tea. Objective: Antioxidant activity of several flavonoids (a group of polyphenols) in figs is higher than that of, vitamin C, glutathione, or vitamin E. Pomegranates contain very high levels of polyphenols as compared to other fruits and vegetables. It is used in folklore medicine for the treatment of various diseases, such as hepatic damage, snakebite, ulcer, etc. Method: The health-positive potential of pomegranate fruit has been mainly attributed to ellagitannins, the predominant class of phenolics in pomegoxidation. Results: The chief phenolic compound found in fresh olive is the bitter secoiridoid oleuropein.. Conclusions: Processing of table olive decreases levels of oleuropein with correlated increases in the hydrolysis of hydroxytyrosol and tyrosol. Many of the health benefits reported for olives are thought to be associated with the levels of hydroxytyrosol. Date palm represents a staple food in most of the Arabian countries and is commonly consumed in several parts of the world. Highlights: Numerous researches revealed the antibacterial, anti-hyperlipidemic, hepatoprotective, antimutagenic, and nephroprotective activity of date fruits, with reported anticancer and anti-fungal features.